Bacterial Spectrum of Spontaneously Ruptured Otitis Media in a 7-Year, Longitudinal, Multicenter, Epidemiological Cross-Sectional Study in Germany - Imöhl, Matthias; Perniciaro, Stephanie; Busse, Andreas; van der Linden, Mark (Frontiers in Medicine, 2021)
We analyzed middle ear fluid (MEF) and nasopharyngeal swabs (NPS) from spontaneously ruptured acute otitis media (AOM) cases occurring in children under 5 years in Germany. The aim of the study was the assessment of disease burden and bacterial etiology in the era of routine pneumococcal vaccination. Furthermore, we aimed to compare isolates from MEF with isolates from NPS and to analyze the Streptococcus pneumoniae serotype distribution. We analyzed MEF and NPS samples in children 2 months to 5 years for vaccination status, frequency of bacterial strains, serotype/emm-type distribution of S. pneumoniae, Haemophilus influenzae, and Streptococcus pyogenes; and intraindividual correlation between MEF and NPS. From 2008 to 2014, MEF samples were collected from 2,138 subjects of which 2,001 (93.6%) also provided an NPS sample. In 851 of 2,138 MEF samples (39.8%), we identified organisms with confirmed pathogenic potential—S. pyogenes: 315 (14.7%), S. pneumoniae: 170 (8.0%), Staphylococcus aureus: 168 (7.9%), H. influenzae: 133 (6.2%), and Moraxella catarrhalis. Among NPS samples, 1,018 (50.9%) contained S. pneumoniae, 775 (38.7%) H. influenzae, 648 (32.4%) M. catarrhalis, and 344 (17.2%) S. pyogenes. Over the seven study years, the number of AOM patients steadily decreased, while the recruiting base remained constant. S. pneumoniae MEF isolates decreased by 86%, with serotype 3 being the most prevalent (25.7–42.9%). PCV13-non-PCV7-non-3 serotypes reduced to 0%. Among NPS, PCV7 serotypes decreased from 14.1 to 3.7%, PCV10: 17.6 to 3.7%, and PCV13: 55.3 to 25.7%. PCV13-non-PCV7-non-3 serotypes increased in the first 3 years of the study (17.1–22.9%), then decreased to 4.6% in year 7. Non-typeable H. influenzae reduced from 87.1 to 41.7% in MEF and from 91.4 to 54.2% in NPS. MEF and NPS isolates from the same subject were identical for 91.9% of S. pneumoniae, 99.0% of S. pyogenes, and 83.3% of H. influenzae. Among PCV7-vaccinated children, 5.6% had a PCV7 vaccine type in the MEF sample, and among PCV13-vaccinated children, 51.7% had a PCV13 serotype. Among non-vaccinated children, the percentages were 14.8 and 70.4. Pneumococcal conjugate vaccination has impacted the prevalence and etiology of spontaneously ruptured otitis media among children in Germany. Overall case numbers and pneumococcal vaccine type cases have strongly decreased.